Pengaruh Absen, Etika, dan Kinerja terhadap Penentuan Karyawan Terbaik di Lingkungan Kerja dengan Metode AHP - Eneng Iviq Hairo Rahayu; Wahyudin, Wahyudin; Lilik Yuliawati; Dinah, Dinah; Zahra, Zahra (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The process of selecting the best employees is complex and requires careful consideration and evaluation. Identifying the best employees is a crucial strategy for enhancing productivity and work motivation within a company. Factors such as absenteeism, work ethic, and performance are often key indicators in assessing employee contributions. This study aims to analyze the influence of these three factors on the selection of the best employees using the Analytic Hierarchy Process (AHP) method. The research sample consisted of 3 employees at PT. Central Jakarta. Data were collected through questionnaires, observations, and interviews. The results showed that in determining the best employees based on the criteria of absence, performance, and ethics, Desta had the highest priority score of 0.351, Wisnu had the second priority score of 0.342, and Dinda had the lowest priority score of 0.307. This research is expected to provide theoretical benefits, enriching the study of the application of the AHP Analytic Hierarchy Process method in the field of human resource management, particularly in the context of employee performance assessment with specific and practical criteria. It also helps PT. Central Jakarta develops a more objective, transparent, and data-driven employee assessment system, thereby supporting increased motivation and effective decision-making within the company.